Effects of long-term management practices on grassland plant assemblages in Mediterranean cork oak silvo-pastoral systems - Bagella, Simonetta; Salis, Lorenzo; Marrosu, Gian Marco; Rossetti, Ivo; Fanni, Stefania; Caria, Maria Carmela; Roggero, Pier Paolo (PLANT ECOLOGY, 2013)
The assessment of the effects of long-term management practices is relevant in understanding the current patterns of plant assemblages in semi-natural ecosystems. We hypothesized that the variety of management practices across different farming systems under the same ecological conditions directly and indirectly shapes these patterns via the long-term changes induced in soil features. The aims of this paper were to evaluate the influence of two sets of variables describing long-term management practices and soil features on plant assemblages and their importance in the context of Mediterranean silvo-pastoral systems. The analysis of variance revealed that richness and grazing value were not affected at all by grazing livestock species and soil tillage frequency and that they both showed relatively high absolute values for the specific context under study. Trifolium subterraneum was a key species in contributing to grassland grazing value and habitat biodiversity. The Canonical Correspondence Analysis highlighted the influence of management practices and soil features on plant assemblage composition, which was significantly affected by grazing livestock species and stocking rate and by soil pH and K content. The Redundancy Analysis showed that soil pH and related features were in turn affected by stocking rate, supporting our hypothesis that management practices influenced plant assemblage composition directly and indirectly via their long-term effects on soil features. The results also highlighted that a systemic analytical perspective applied at a grazing system scale can be effective in addressing sustainable grassland management issues in Mediterranean silvo-pastoral systems.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: grazing systems; soil features; Stocking rate; Tillage; Trifolium subterraneum

Comparative Typology in Six European Lowâ€Intensity Systems of Grassland Management - Caballero, Rafael; Riseth JÅand Labba, Niklas (Advances in Agronomy, 2007)
management with varying degrees of arrangements in different European countries and landscapes. These large-scale grazing systems (LSGS) are rein- deer husbandry in Northern Sapmi (Fennoscandia), sheep grazing in the Polish Tatra mountains, cattle grazing in the Swiss and German Alps, cattle, sheep, and pig grazing in Baixo Alentejo, Southern Portugal, and sedentary sheep grazing in Central Spain. These systems showed very heterogeneous organizational patterns in their way of exploiting the pastoral resources. At the same time, these LSGS showed at least some of the following weaknesses such as poor economic performance, social fragility, and structural shortcomings for proper grazing management. Lack of proper mobility of herds/flocks or accession to specific grazing grounds can be a cause of environmental hazards. The sur- veyed LSGS are mostly dependent on public handouts for survival, but succes- sive policy schemes have only showed mixed effects and, in particular study areas, clear inconsistencies in their aim to stop the general declining trend of LSGS. This research assumed that detailed system research may open the way for better-focused policy intervention, but policymakers need to take advantage of this period of support to push ahead for reforms. Recent European Union (EU) guidelines (2007–2013) on Rural Development Policy (RDP) and its operative scale of high nature value (HNV) farmland can easily fit the structure and functions of low-input grazing systems and LSGS.
Keywords: economic performance; Grazing lands; Grazing management; grazing systems; land use; productivity (voyant)

Comparative Typology in Six European Lowâ€Intensity Systems of Grassland Management - Caballero, Rafael; Riseth JÅand Labba, Niklas (Advances in Agronomy, 2007)
management with varying degrees of arrangements in different European countries and landscapes. These large-scale grazing systems (LSGS) are rein- deer husbandry in Northern Sapmi (Fennoscandia), sheep grazing in the Polish Tatra mountains, cattle grazing in the Swiss and German Alps, cattle, sheep, and pig grazing in Baixo Alentejo, Southern Portugal, and sedentary sheep grazing in Central Spain. These systems showed very heterogeneous organizational patterns in their way of exploiting the pastoral resources. At the same time, these LSGS showed at least some of the following weaknesses such as poor economic performance, social fragility, and structural shortcomings for proper grazing management. Lack of proper mobility of herds/flocks or accession to specific grazing grounds can be a cause of environmental hazards. The sur- veyed LSGS are mostly dependent on public handouts for survival, but succes- sive policy schemes have only showed mixed effects and, in particular study areas, clear inconsistencies in their aim to stop the general declining trend of LSGS. This research assumed that detailed system research may open the way for better-focused policy intervention, but policymakers need to take advantage of this period of support to push ahead for reforms. Recent European Union (EU) guidelines (2007–2013) on Rural Development Policy (RDP) and its operative scale of high nature value (HNV) farmland can easily fit the structure and functions of low-input grazing systems and LSGS.
The following values have no corresponding Zotero field: periodical: Advances in Agronomy electronic-resource-num: 10.1016/S0065-2113(07)96001-0
Keywords: economic performance; Grazing lands; Grazing management; grazing systems; land use; productivity (voyant)

Change in plant spatial patterns and diversity along the successional gradient of Mediterranean grazing ecosystems - Alados, Concepción L.; ElAich, Ahmed; Papanastasis, Vasilios P.; Ozbek, Huseyin; Navarro, Teresa; Freitas, Helena; Vrahnakis, Mihalis; Larrosi, Driss; Cabezudo, Baltasar (Ecological Modelling, 2004)
In this study, we analyze the complexity of plant spatial patterns and diversity along a successional gradient resulting from grazing disturbance in four characteristic ecosystems of the Mediterranean region. Grazing disturbance include not only defoliation by animals, but also associated disturbances as animal trampling, soil compaction, and mineralization by deposition of urine and feces. The results show that woodland and dense matorral are more resistant to species loss than middle dense and scattered matorral, or grassland. Information fractal dimension declined as we moved from a dense to a discontinuous matorral, increasing as we moved to a more scattered matorral and a grassland. In all studied cases, the characteristic species of the natural vegetation declined in frequency and organization with grazing disturbance. Heliophyllous species and others with postrate or rosette twigs increased with grazing pressure, particularly in dense matorral. In the more degraded ecosystem, only species with well-adapted traits, e.g., buried buds or unpalatable qualities showed a clear increase with grazing. Indeed, the homogeneity of species distribution within the plant community declined monotonically with grazing impact. Conversely, the spatial organization of the characteristic plants of each community increased in the better-preserved areas, being also related to the sensitivity of the species to grazing impact. The degree of autocorrelation of plant spatial distribution at the species level and the information fractal dimension at the community level allow us to quantify the degree of degradation of natural communities and to determine the sensitivity of key species to disturbance.
Keywords: fractal analysis; grazing systems; spatial patterns

Change in plant spatial patterns and diversity along the successional gradient of Mediterranean grazing ecosystems - Alados, Concepción L; ElAich, Ahmed; Papanastasis, Vasilios P; Ozbek, Huseyin; Navarro, Teresa; Freitas, Helena; Vrahnakis, Mihalis; Larrosi, Driss; Cabezudo, Baltasar (Ecological Modelling, 2004)
In this study, we analyze the complexity of plant spatial patterns and diversity along a successional gradient resulting from grazing disturbance in four characteristic ecosystems of the Mediterranean region. Grazing disturbance include not only defoliation by animals, but also associated disturbances as animal trampling, soil compaction, and mineralization by deposition of urine and feces. The results show that woodland and dense matorral are more resistant to species loss than middle dense and scattered matorral, or grassland. Information fractal dimension declined as we moved from a dense to a discontinuous matorral, increasing as we moved to a more scattered matorral and a grassland. In all studied cases, the characteristic species of the natural vegetation declined in frequency and organization with grazing disturbance. Heliophyllous species and others with postrate or rosette twigs increased with grazing pressure, particularly in dense matorral. In the more degraded ecosystem, only species with well-adapted traits, e.g., buried buds or unpalatable qualities showed a clear increase with grazing. Indeed, the homogeneity of species distribution within the plant community declined monotonically with grazing impact. Conversely, the spatial organization of the characteristic plants of each community increased in the better-preserved areas, being also related to the sensitivity of the species to grazing impact. The degree of autocorrelation of plant spatial distribution at the species level and the information fractal dimension at the community level allow us to quantify the degree of degradation of natural communities and to determine the sensitivity of key species to disturbance.
Keywords: fractal analysis; grazing systems; spatial patterns